Synthesizing Liquid Fuels Over Carbon‐Based Catalysts Via CO2 Conversion - Cederick Cyril Amoo; Qingjie Ge; Vitaly Ordomsky; Jian Sun (Advanced Science)
Abstract The unique characteristics of carbon materials make them flexible for applications in heterogeneous catalysis. Their interest is expanding in the conscious efforts being made toward sustainable fuel production. A notable application is the heterogenous conversion of CO2 to liquid fuels, which exploits the characteristics of carbon materials, taking advantage of their electronic configurations, high surface area, pore properties, and synergistic role in catalysis. In this review, a critical overview of this rapidly developing field is presented. Various carbon allotropes and derivatives, as well as some strategies for fabricating carbon‐based catalysts are keenly highlighted within thermal‐, electro‐, and photocatalytic CO2 conversion to liquid fuels. Distinct emphasis is placed on the role of different carbon materials by investigating the unique synergy attained at catalyst interfaces, the physicochemical properties attained, and their influence in enhancing the specific liquid fuels synthesis. Finally, the work is concluded, followed by an outlook detailing key challenges that need addressing.